A rare vasculitis with a dramatic presentation: Acute hemorrhagic edema of infancy - Vineet Relhan; Jaspriya Sandhu; Vijay Kumar Garg; Nita Khurana (Wolters Kluwer Medknow Publications, 2020)
Acute hemorrhagic edema of infancy is a disease marked by its dramatic presentation of purpuric plaques in a cockade or targetoid pattern. A 1-year-old boy was brought by his mother to our outpatient department with large purpuric plaques in annular and cockade pattern over the cheeks and bilateral lower limbs. Both the pinna showed purpura in a peculiar reticulate pattern, with vesiculation seen at the margin of the lesions along with mild edema. The skin biopsy showed cutaneous small-vessel vasculitis; direct immunofluorescence showed fibrinogen deposits around the small cutaneous vessels. The unusual features of our case were the reticulate pattern of purpura seen over the ears.